EVALUATION OF SNAG DENSITY AND UTILIZATION BY WILDLIFE IN MAYOSELBE RANGE OF GASHAKA GUMTI NATIONAL PARK, NIGERIA - JOSEPH, J.; TIMOTHY, C.S.; KHOBE, D.; BUBA, Z.M., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Snags (standing dead trees) have numerous ecological functions and contribute to structural complexity and biodiversity in terrestrial habitats. A wide variety of wildlife depends on snags for survival and reproduction. A study conducted to evaluate snag density and utilization by wildlife species at Mayo-Selbe Range of Gashaka Gumti National Park. A total of 30 sample plots measuring 50 by 50 feet were obtained randomly using stratified random sampling technique. The density of snags was determined by counting from each of the plots, while organisms visible on or within the snags were recorded. Data was analysed using descriptive statistics. A total of 161 snags were recorded from the 30 sample plots, that is an average of 5 snags per 50 by 50 feet plot, while 26 species/categories of living organisms were found inhabiting the snags. Species of insects (ants and termites), green alga such as spirogyra and mushrooms were the most occurring organisms found inhabiting the snags, while small mammals such as bats, reptiles such as snakes and arthropods (centipedes and millipedes) were rarely found. The organisms identified on the snags have successfully carved niches for their sustenance. They depended on the snags for shelter (habitat), reproductive activities, roosting/resting, feeding and hiding/refuge. Though, the snag density was adequate, minimal use of the snags by birds such as woodpeckers was observed. This may be attributed to hunting pressure or other environmental factors. It is recommended that the management of the Park should intensify effort to ensure that the snags are allowed to thrive and not exploited for fuelwood (firewood) or other purposes. In addition, efforts need to be made in ensuring the protection of biological resources of the Gashaka Gumti National Park.